Heart Shaped Anterior Neck Lipoma Mimicking Thyroid Mass: A Case Report - Abdus Samad Ansari; Dhiraj Chaurasia; Bikash Yadav; Season Shrestha; Inku Shrestha Basnet (Clinical Case Reports)
ABSTRACT Lipomas, one of the most common benign tumors, rarely occur in the anterior neck, often misdiagnosed as thyroid masses. This case highlights the diagnostic challenge posed by such lesions. A 58‐year‐old male presented with a painless slowly progressive anterior neck swelling initially mistaken for a thyroid mass. Though clinical examination findings suggested lipoma, the location of swelling influenced the decision toward thyroid mass. The elevated thyroid stimulating hormone (TSH) level further inclined the diagnosis toward thyroid mass. But imaging and fine needle aspiration cytology shifted the diagnosis toward a lipoma. Surgical excision was performed successfully. The gross and histopathological examination confirmed the diagnosis of lipoma. Anterior neck lipomas pose diagnostic challenges due to their uncommon location. Thorough clinical examination and evaluation is crucial to differentiate them from other neck pathologies, primarily thyroid mass. Surgical excision remains the preferred treatment. Postoperative follow‐up is important to monitor for recurrence and complications. Awareness of anterior neck lipoma is vital among clinicians for early diagnosis and optimal management. Early suspicion of this prevalent condition in the given unusual location can guide them towards appropriate diagnostic approach and treatment decisions, ultimately improving patient outcomes and reducing diagnostic complexity for healthcare professionals.